Thực trạng ô nhiễm môi trường làng nghề cơ khí ở xã Nam Giang - Lài, Lê Thị; Kasbohm, Joern; Eidam, Juergen (Vietnam Journal of Earth Sciences, 2000)
Assessement of evironmental pollution in metalprocessing village of Nam Giang (Nam Dinh)